ANALISIS JARINGAN KOMUNIKASI OPINI PUBLIK PADA FENOMENA “PEMECATAN Dr TERAWAN” DI TWITTER - Agus Rafi Al Majid; Widyo Nugroho (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2022)
This study aims to determine the system-level communication network and actors on the “Terawan” link and to find out public opinion about this phenomenon and how the IDI organization reacts in responding to public opinion. By using the theory of Computer Mediated Communication (CMC). The method used in this research is a quantitative approach with the method of Social Network Analysis with Netlytic and Gephi and content analysis. The population used in this study are active Twitter users, with a maximum sample of 2500 obtained from Netlytic. The results showed that this network has 1969 Nodes and 1991 Edges, with 5 large clusters in this network. This network has a value of Diameter 19, Destiny 0.000604, Reciprocity 0.011160, Centralization 0.107200 and Modularity 0.810800. The most influential actor in this network is @heraloebs with a Degree Centrality value of 391 and an Eigenvector Centrality value of 1.0. Therefore, this network includes a network that is widespread in the distribution of information, with influential actors in the distribution of information such as @heraloebss. While the focus of communication carried out by the IDI organization in responding to public opinion regarding the phenomenon of “Dr Terawan’s dismissal”